2010
DOI: 10.1073/pnas.1001763107
|View full text |Cite
|
Sign up to set email alerts
|

Inferring individual rules from collective behavior

Abstract: Social organisms form striking aggregation patterns, displaying cohesion, polarization, and collective intelligence. Determining how they do so in nature is challenging; a plethora of simulation studies displaying life-like swarm behavior lack rigorous comparison with actual data because collecting field data of sufficient quality has been a bottleneck. Here, we bridge this gap by gathering and analyzing a high-quality dataset of flocking surf scoters, forming wellspaced groups of hundreds of individuals on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
388
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 394 publications
(403 citation statements)
references
References 33 publications
12
388
3
Order By: Relevance
“…To be more than a powerful visualization tool, this approach has to demonstrate its ability to lead to a model that would reproduce in turn the experimental data. A partial answer is given by the work done by Lukeman et al [82], that quantitatively reproduces at the collective level the behaviour of surf scoters, thanks to a selfpropelled particles model with an additional frontal preference hypothesis. However, without an agreement of the model at the individual level, it is difficult to evaluate to which extent the extracted behavioural algorithm corresponds to the actual behaviour-in this case, the value of the frontal preference hypothesis.…”
Section: Inferring Interactions Between Individualsmentioning
confidence: 99%
See 2 more Smart Citations
“…To be more than a powerful visualization tool, this approach has to demonstrate its ability to lead to a model that would reproduce in turn the experimental data. A partial answer is given by the work done by Lukeman et al [82], that quantitatively reproduces at the collective level the behaviour of surf scoters, thanks to a selfpropelled particles model with an additional frontal preference hypothesis. However, without an agreement of the model at the individual level, it is difficult to evaluate to which extent the extracted behavioural algorithm corresponds to the actual behaviour-in this case, the value of the frontal preference hypothesis.…”
Section: Inferring Interactions Between Individualsmentioning
confidence: 99%
“…Besides their success in linking functional properties at the school level to behavioural mechanisms at the individual scale and some experimental success [82,83], it is unlikely that the self-propelled particles framework, as we defined it, has the ability to lead to models accurately reproducing experimental data of species, notably in explaining the experimental speed distributions and consequently the mechanisms responsible for speed synchronization. In particular, a series of simulation studies have shown that the mean speed of an individual could be considered as an emergent property as well [51,69,74].…”
Section: Social Forces Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn allows groups to maintain their coherence and enables group members to realize the benefits of group living [7]. To date, however, most studies of collective behaviour have assumed that group members are identical in their movements and responses to their neighbours [2][3][4] (but see [8][9][10] for theoretical predictions and [11,12] for empirical observations about individual differences in groups). This common assumption of homogeneity contrasts with a large and growing body of work documenting consistent inter-individual differences in behaviour [13][14][15][16][17][18] and evidence that differences in the social affiliations between group members, and individual differences, can affect leadership and the collective decision-making process [12,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Group-level properties, such as the collective movements of animal groups, emerge when individuals respond to the location and movements of their near neighbours [2][3][4]. This responsiveness to the behaviour of neighbours allows consensus to be reached over the timing and direction of group movements [5,6].…”
Section: Introductionmentioning
confidence: 99%